2014
DOI: 10.1002/pri.1595
|View full text |Cite
|
Sign up to set email alerts
|

Gait Changes with Balance‐Based Torso‐Weighting in People with Multiple Sclerosis

Abstract: Background and Purpose People with multiple sclerosis (PwMS) commonly have mobility impairments that may lead to falls and limitations in activities. Physiotherapy interventions that might improve mobility typically take several weeks. Balance-based torso-weighting (BBTW), a system of strategically placing light weights to improve response to balance perturbations, has resulted in immediate small improvements in clinical measures in PwMS, but changes in spatio-temporal gait parameters are unknown. The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
(45 reference statements)
0
5
0
1
Order By: Relevance
“…Our findings indicate that a mechanism other than a pure biomechanical shift appears to underlie BBTW. Gait data from these participants revealed that weighting increased gait velocity (p=0.002) compared to gait without weight, 14 indicating that BBTW did have an effect. Any proposed alternative mechanism must account for the apparent integration of sensory stimuli provided by these strategically placed light weights and consequent adjustment of postural sway, improvements in stability with perturbations and rotational forces, and increases in gait velocity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our findings indicate that a mechanism other than a pure biomechanical shift appears to underlie BBTW. Gait data from these participants revealed that weighting increased gait velocity (p=0.002) compared to gait without weight, 14 indicating that BBTW did have an effect. Any proposed alternative mechanism must account for the apparent integration of sensory stimuli provided by these strategically placed light weights and consequent adjustment of postural sway, improvements in stability with perturbations and rotational forces, and increases in gait velocity.…”
Section: Discussionmentioning
confidence: 87%
“…This investigation was part of a larger study that involved motion analysis of gait in unweighted and weighted conditions. 14 …”
mentioning
confidence: 99%
“…Balance is an important part of rehabilitation [ 37 ] because falls are a major predisposing factor for fractures and death in the elderly [ 38 , 39 ]. It is well known that the loss of a foot or leg can reduce balance and impair gait [ 18 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro estudio, en la figura 5 se aprecia como el sujeto que ha obtenido más mejoras en la prueba del equilibrio estático lateral (tarea que más se identifica con el test que se ha pasado), la cual trata de cambiar el peso corporal de lado, aspecto cuya importancia fue medida en el estudio de Gorgas (2015), resultando tener una transferencia directa a la mejora y estabilidad de la marcha, ha sido el participante número 1, siendo este el único hombre, con la consiguiente contradicción de la afirmación de García-Pedroza ( 2003) respecto a que ser del género masculino es un factor negativo en la EM, pero hay que añadir que se trata del sujeto que lleva menos número de años con la enfermedad, no siendo este un factor relevante, puesto que el único participante que no experimenta mejoras en dicha tarea es el número 4 el cual, después del an-terior, es el que lleva menos tiempo con la enfermedad, pudiendo comprobar que en cuanto a la progresión de la EM no existen dos pacientes iguales (Arroyo, 2017) aunque en la actualidad ambos convivan con el mismo tipo de EM, siendo esta del tipo EMRR. Todos los demás, en mayor o menor medida, han alcanzado progresos en los valores obtenidos en dicha prueba al final del entrenamiento con respecto al comienzo del mismo.…”
Section: Discussionunclassified